PREDICTION OF CLEAN WATER SUPPLY FOR MARINE SUPPLIES AT THE BUNGUS OCEAN FISHING PORT USING FUZZY LOGIC - Andre Adrian Mauhid; Bustari Bustari; Arthur Brown (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTPelabuhan Perikanan Samudera Bungus has provided and determined the same amount of clean water every month but a strategy is needed to predict the supply of clean water by the port using the fuzzy logic method so as not to experience a shortage in providing clean water for fishing supplies.The results of the study show that the predicted results of clean water supply have increased compared to the clean water supply in 2019.The total supply of clean water in 2019 is 1150 Ton  and the prediction results obtained are 1179,63 Ton.Prediction results for clean water supplies are obtained by month, namely from January to December, the results are the same or only in August.Based on the MSE results obtained, it produces a fairly large error in the prediction results, which is 630.0103. Although there is a fairly large error, the prediction results can be accepted and used to determine the supply of clean water for fishing supplies.Keywords: Clean Water Supply Prediction, Fishing Supplies, Fuzzy Logic